(untitled) (Journal of Science and Technology, 2016)
This paper seeks to introduce as briefly as possible to the Ghanaian academic world, a most interesting subject that has so far escaped our notice, despite its existence for more than half century in Europe and America. It is the subject of Art Therapy, which draws its roots from fields as Art, Art Education, Psychology and Psychotherapy. Art therapy is used mainly in psychiatric health units, day centers or places of rehabilitation for people recovering from mental illness and also in schools, and private practice. Some of its theoretical roots have very interesting implications for further research in the Ghanaian and African contexts.